Modal Models of Social Behavior of Medical Care Consumers in the Russian Society - LUBSKY, Anatoly; VYALYKH, Nikita (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
The paper suggests a new methodological construct of the neoclassical model of sociological research, which is based on the principle of constructive realism. In the framework of this construct, the model of social behavior is a cognitive analogue of the practices of social behavior as a person's response to the social situation in the form of certain social actions conditioned by the mental program structures. Modal models of social behavior of medical care consumers are determined by such structures of these programs, which are of a reflexive character. The peculiarities of alternative (conservative and liberal) and hybrid (conservative-liberal and liberal-conservative) modal models of the social behavior of medical care consumers in the modern Russian society are considered, the availability which is explained by the difficulties of transition from the budgetary system of health care to the budget-insurance one for the Russian society.